THE EFFECT OF GREEN PRODUCT AND SOCIAL MEDIA MARKETING ON THE PURCHASE DECISION OF PRODUCTS IN PT. SENSATIA BOTANICALS - Ni Luh Bayu Okadiani; Ni Wayan Eka Mitariani; I Gusti Ayu Imbayani (AIBPM Publisher, 2019)
The green product is a product that is not harmful to humans and the environment, not wasteful of resources, does not produce excessive waste and involves cruelty to animals, green products must consider environmental aspects in the product life cycle so as to minimize negative impacts on nature. While social media marketing is one form of marketing using social media to market a product, service, brand or issue by utilizing audiences who participate in social media so that later it will produce purchasing decisions. In this study using a nonprobability sampling method with a number of 100 respondents. The results of this study found that green products have a positive and significant effect on purchasing decisions at PT. Sensatia Botanicals with the regression value of the green product variable is 0.614. Whereas social media marketing does not have a significant effect on purchasing decisions at PT. Sensatia Botanicals with the regression coefficient value of social media marketing variables of - 0,110.